Overexpression of KIF23 predicts clinical outcome in primary lung cancer patients. (February 2016) - Kato, Tatsuya; Wada, Hironobu; Patel, Priya; Hu, Hsin-pei; Lee, Daiyoon; Ujiie, Hideki; Hirohashi, Kentaro; Nakajima, Takahiro; Sato, Masaaki; Kaji, Mitsuhito; Kaga, Kichizo; Matsui, Yoshiro; et al.
Highlights: The high level of KIF23 expression was observed in majority of metastatic lung cancer tissue compared with normal lung control. KIF23 is crucial for the growth and survival of lung cancer cells. A high level of the KIF23 is strongly associated with poor survival in patients with lung adenocarcinoma. KIF23 can be valuable for developing new therapeutic targets for advanced lung cancers. Abstract: Objective: High-level expression of kinesin family member 23 (KIF23), a member of microtubule-dependent molecular motors that transport organelles within cells and move chromosomes during cell division, has been observed in a variety of human malignancies. The aims of the present study were to observe the expression of KIF23 in lung cancer, examine the role of KIF23 in lung cancer cell growth and/or survival by small interfering RNA experiments, and explore its clinicopathologic significance and evaluate KIF23 expression as a prognostic marker. Materials and methods: Quantitative reverse transcription-polymerase chain reaction analysis was performed to detect the expression of KIF23 mRNA using metastatic lymph nodes from patients with advanced lung cancer obtained by endobronchial ultrasonography-guided transbronchial needle aspiration (EBUS-TBNA) and primary lung tumors through surgical sample. The role of KIF23 in cancer cell growth was examined by small interfering RNA experiments. A total of 339 lung cancers were analyzed immunohistochemically on tissue microarrays to examine the expression of KIF23 protein and its clinicopathologic significance. Results: KIF23 transcript was found to be overexpressed in the great majority of metastatic lymph nodes from advanced lung cancers and primary lung tumors. Inhibiting KIF23 expression effectively suppressed lung cancer cell growth. High-level KIF23 expression was observed in 67.8% of the 339 cases. Lung adenocarcinoma patients with tumors displaying a high-level of KIF23 expression was also identified as an independent prognostic factor by multivariate analysis ( P = 0.0064). Conclusion: KIF23 not only provides additional prognostic information for surgical treatment of lung cancer, but may also be a novel therapeutic target for these patients.